Implementasi Teori Strategi Lempar Bola (Floring Ball) Dalam Mengembangkan Sosial Emosional - Hanifah Syahputri; Wardiyani Abdillah Hutasuhut; Wirdatunnafiah Harahap; Siti Diah Hartinah (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to find out how to apply the theory of safe, easy and interesting ball throwing strategies and innovations to improve the social emotional development of children aged 5-6 years. With this theory is also expected to produce games that can help improve the development of social emotional aspects of children aged 5-6 years. This study also aims to determine the strategies used by teachers in applying the theory of throwing a ball to help improve the social emotional development of children aged 5-6 years. This research was conducted in RA. Al-Mukhlisin Jl. Kedondong, Marindal Village, I Kec. Patumbak Kab. Deli Serdang with 15 children as the subject. This research method uses qualitative methods